2019
DOI: 10.18203/2349-2902.isj20191257
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of wound healing in relation to nutritional status of the patients in common surgical condition in tertiary care centre

Abstract: Background: Wound healing depends upon a balance between general factors which include nutritional status of the patient and local factors. Assessment of wound healing in relation to nutritional status of the patients in common surgical conditions.Methods: 46 surgical patients admitted in S.R.N. Hospital, Motilal Nehru Medical College, Allahabad during the period from July 2017 to July 2018, were included. Clinical, anthropometric examination, assessment of wound healing and factors affecting wound healing was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…In this study nutritional status was found to be significantly associated with wound healing outcomes. This result was in agreement with other studies done in India [ 14 ], Italy [ 22 ], India [ 15 ], and Korea [ 21 ]. This finding could be explained by the fact that the patients had a good nutritional status which enhances the growth hormone and collagen production that increase tensile strength and decrease risk factor of wound healing dalliance.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study nutritional status was found to be significantly associated with wound healing outcomes. This result was in agreement with other studies done in India [ 14 ], Italy [ 22 ], India [ 15 ], and Korea [ 21 ]. This finding could be explained by the fact that the patients had a good nutritional status which enhances the growth hormone and collagen production that increase tensile strength and decrease risk factor of wound healing dalliance.…”
Section: Discussionsupporting
confidence: 94%
“…In this study nutritional status was found to be significantly associated with wound healing outcomes. is result was in agreement with other studies done in India [14], Italy [22], India [15], and Korea [21].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The main purpose of wound management is to assure healthy on-time wound healing, which could assure by maintaining a balance between different wound factors (local and general). [1][2][3][4] This balance between local and general factors shall assure by regular monitoring of wound. This regular check on biological on-going wound healing mechanism will ultimately prevent wound from infection, inappropriate tissues regeneration and impaired healing.…”
Section: Introductionmentioning
confidence: 99%